Occurrence and characterization of methicillin-resistant Staphylococcus pseudintermedius in successive parturitions of bitches and their puppies in two kennels in Italy - Michela Corrò; Joakim Skarin; Stefan Börjesson; Ada Rota (BMC Veterinary Research, 2018)
Abstract Background Multi-drug methicillin-resistant Staphylococcus pseudintermedius (MRSP) detection is rapidly increasing in microbial specimens from pets across Europe. MRSP has also been isolated from bitches and newborns in dog breeding kennels. This study assessed whether MRSP lineage differs between breeding kennels and is maintained over time. Post-partum bitches (at day 3 vaginal and day 3, 9 and 35 milk samples) and their litters (at day 3, 9 and 35 oral and abdominal skin samples) from two Italian breeding kennels (A and B) were sampled and MRSP was subsequently characterized via whole-genome sequencing and antibiotic susceptibility testing. The study was carried out from October 2014 to March 2016 and included successive parturitions from the same animals. Results The analysis revealed different situations in both investigated kennels. In kennel A, circulating strains were from 7-locus sequence types ST688, ST258 and closely related isolates of ST71, which included most isolates. In kennel B, only a new isolate, ST772, was detected. In addition, most isolates from both kennels had multi-resistant antibiotic profiles. MRSP was only isolated from litters of MRSP-positive bitches, thus suggesting that bitch-litter transmission is likely. Conclusions Our data show that MRSP circulation can differ in different settings, that several clonal lineages can circulate together, and that vertical transmission appears common. MRSP colonization did not affect the health conditions of the bitches or of their litters.